1995
DOI: 10.1007/bf00571098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a masked stimulus on the response to the masking stimulus

Abstract: Four experiments are reported in which the subjects had to respond to a target that masked a preceding prime via metacontrast masking. In one part of Experiment 1, the subjects discriminated the target's shape (square or diamond) by a motor-choice reaction, and in another part they had to respond with a simple reaction. The prime was neutral (circular) with respect to the target's shape. The data showed a facilitation effect. In both tasks the reaction time was reduced by the masked prime. However, the reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
84
1
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 21 publications
8
84
1
3
Order By: Relevance
“…In line with this hypothesis, evidence has been found that even stimuli presented near or below the threshold of conscious awareness can trigger response activation processes (Dehaene et al, 1999;Klotz & Wolff, 1995;Neumann & Klotz, 1994;Schwarz & Mecklinger, 1995). These phenomena have been attributed to the existence of direct perceptuomotor links (Neumann, 1990), which allow perceptual information to affect the motor system directly without necessarily being consciously perceived.…”
mentioning
confidence: 87%
“…In line with this hypothesis, evidence has been found that even stimuli presented near or below the threshold of conscious awareness can trigger response activation processes (Dehaene et al, 1999;Klotz & Wolff, 1995;Neumann & Klotz, 1994;Schwarz & Mecklinger, 1995). These phenomena have been attributed to the existence of direct perceptuomotor links (Neumann, 1990), which allow perceptual information to affect the motor system directly without necessarily being consciously perceived.…”
mentioning
confidence: 87%
“…The time course of stimulus-triggered motor activation can be studied in response-priming tasks (Klotz & Neumann, 1999;Klotz & Wolff, 1995;Vorberg, Mattler, Heinecke, Schmidt, & Schwarzbach, 2003). In a typical response-priming task, participants perform a speeded response to a target stimulus that is preceded by a prime stimulus triggering either the same response as the target (consistent prime) or the opposite response (inconsistent prime).…”
Section: Motor Activation In Response Primingmentioning
confidence: 99%
“…If the target (the greyscales images) was presented briefly, and then a similarly shaped mask was presented following a short delay (see Klotz & Wolff, 1995 for example), it would strengthen the evidence in support of the task being purely attentional and not based on the participant"s memory of the image. It is recommended that a mask of similar shape be used as reaction times are typically faster and the number of errors is smaller when the target and the mask are congruent (Klotz & Wolff, 1995). This paradigm would eliminate concerns related to scanning and, more importantly, regarding mental representations that might have been formed.…”
Section: New Directions For Future Workmentioning
confidence: 99%